Legal rights of people with cancer: knowledge of users of a public service of oncology - Luis Filipe Alves da Rosa; Nara Marilene Oliveira Girardon-Perlini; Bruna Stamm; Manuela da Silva Couto; Andreza Lima Cardoso; Noeli Maria Birk (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769213002 Aim: to verify the knowledge of patients with cancer in treatment at the oncology service of a public university hospital about their legal rights. Method: this study is descriptive and exploratory and has a quantitative approach. It was performed in the chemotherapy and radiotherapy services. The sample consisted of 73 patients undergoing cancer treatment. The data collection occurred from October to November 2013, through a questionnaire containing socio-demographic and clinical questions as well as questions related to the legal rights of cancer patients. Data were analyzed through simple descriptive statistics using the software Epi Info. Results: among the rights, the best known was the sick pay. The means of communication was the most frequently mentioned source of information regarding the right to preferential treatment in establishments. Conclusions: it is concluded that cancer patients have little knowledge of their legal rights, being recommended that the services of oncology invest in information.